Interaction of Myricetin with ds-DNA Analyzed by Spectrophotometry and Cyclic Voltammetry Techniques - Hajian, R.; Iravani, N.; Ghanbari, F.; Shams, N. (Asian Journal of Chemistry, 2012)
Cyclic voltammetry coupled with UV/VIS spectroscopic techniques were used to study the interaction of myricetin, a flovonoid compound, with double stranded calf thymus DNA (ds-DNA) in phosphate buffer solution (pH 7.5). In spectrophotometric studies, maximum absorbance at ca. 330 nm for myricetin does not change significantly by addition of ds-DNA to the solution. The slopes of the calibration curves for methotrexate in the absence and presence of neutral red (NR)-DNA are similar. Because of the inactivity of myricetin on the surface of hanging mercury drop electrode, we used neutral red as a probe for electrochemical study of myricetin with ds-DNA. In the electrochemical study of neutral red, the appearance of a pair redox peaks with DEp = 3.0 mV shows the adsorption process. The decreasing of peak currents for neutral red by addition of ds-DNA reveals a high strength binding between neutral red and DNA (Kb = 2.74 × 104). In the competitive study on the titration of neutral red-DNA with myricetin shows no significant changes on the oxidation or reduction of neutral red-DNA. These studies are valuable addition for a better understanding of the detailed mode of interaction between myricetin with ds-DNA, which should be important in deeper insight into the therapeutic efficacy of myricetin and design of new DNA targeted drugs. All of the electrochemical and spectroscopy studies show that myricetin has a week interaction with ds-DNA.